Situação de segurança alimentar e nutricional no meio rural: um estudo de caso com famílias agricultoras no município de Pato Branco - PR - Barancelli, Anelise Jaeger (2018)
From the analysis of the concept of Food and Nutrition Security (FNS), it is identified that all individuals have the right to regular and permanent access to food and that this in turn, does not compromise other essential needs. The complexity of the FNS phenomenon requires the evaluation of its levels in the population, but, currently, there is no instrument that considers the distinction between the inhabitants of the urban and rural space, and for these two populations the reality regarding food, differs considerably. From this context, the present research aims to analyze the level of food and nutritional (in) safety among the agricultural families of the municipality of Pato Branco - PR. In order to operationalize the evaluation process of the FNS level of the sample, an evaluation tool was developed, presenting four indicators: i) cultivation and availability of food; (ii) access to food; (iii) food consumption; iv) biological use of nutrients. To obtain data, a case study was carried out with a sample of 20 farming families, representing 10 categories of activities carried out in the rural area of the municipality. In order for the answers to be converted into values, they were translated by scoring and the result of each indicator, classified according to a scale of values and categories for the SAN evaluation. Among the 20 families, a family reached a level of 100% Food Security and Nutrition Status (FSNS), where food production in the property for self consumption is directly linked to satisfactory levels of access to food. The lowest level of FSNS reached was 65%, characterizing the high value invested in the acquisition of food from outside the property. When quantifying the average of the indicators, a percentage of 85% of FSNS was obtained, representing an ideal situation in which the set of factors present in the considered dimensions guarantee the FNS right. Although this situation is favorable, actions related to the production of food for self-consumption, as well as actions of primary health care for the rural population should not be relegated.